Efficiency of the pTF-FC2 pas Poison-Antidote Stability System in Escherichia coli Is Affected by the Host Strain, and Antidote Degradation Requires the Lon Protease - Smith, Anthony S. G. (American Society for Microbiology, 1998)
The stabilization of a test plasmid by the proteic, poison-antidote plasmid addiction system (pas) of plasmid pTF-FC2 was host strain dependent, with a 100-fold increase in stability in Escherichia coli CSH50, a 2.5-fold increase in E. coli JM105, and no detectable stabilization in E. coli strains JM107 and JM109. The lethality of the PasB toxin was far higher in the E. coli strains in which the pas was most effective. Models for the way in which poison-antidote systems stabilize plasmids require that the antidote have a much higher rate of turnover than that of the toxin. A decrease in host cell death following plasmid loss from an E. coli lon mutant and a decrease in plasmid stability suggested that the Lon protease plays a role in the rate of turnover of PasA antidote.